2003
DOI: 10.1063/1.1621729
|View full text |Cite
|
Sign up to set email alerts
|

Ga-doped ZnO single-crystal nanotips grown on fused silica by metalorganic chemical vapor deposition

Abstract: In situ Ga-doped ZnO nanotips were grown on amorphous fused silica substrates using metalorganic chemical vapor deposition. Structural, optical, and electrical properties of as-grown ZnO nanotips are investigated. Despite the amorphous nature of fused silica substrates, Ga-doped ZnO nanotips are found to be single crystalline and oriented along the c-axis. Photoluminescence ͑PL͒ spectra of Ga-doped ZnO nanotips are dominated by near-band-edge emission with negligible deep-level emission. The increase in PL int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
87
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(90 citation statements)
references
References 21 publications
1
87
0
Order By: Relevance
“…Ga is well-known as an n-type dopant in ZnO and has been employed to increase the conductivity of ZnO nanorods and nanowires. 4,6,12 However, previous studies employing homogeneous doping of Ga in ZnO 1D nanostructures have reported unintentional effects, including an optical degradation 6,12 and structural deformation. 4,6 Here, we report on the modulation-doping technique to control electrical characteristics of ZnO nanorods for field effect transistor ͑FET͒ applications.…”
mentioning
confidence: 98%
“…Ga is well-known as an n-type dopant in ZnO and has been employed to increase the conductivity of ZnO nanorods and nanowires. 4,6,12 However, previous studies employing homogeneous doping of Ga in ZnO 1D nanostructures have reported unintentional effects, including an optical degradation 6,12 and structural deformation. 4,6 Here, we report on the modulation-doping technique to control electrical characteristics of ZnO nanorods for field effect transistor ͑FET͒ applications.…”
mentioning
confidence: 98%
“…Reports on the applications of semiconducting-metal oxides as gas sensors continue to grow due to the benefits of small dimensions, low cost, and high compatibility with microelectronic processing [7,8]. Furthermore, ZnO-based semiconductor materials have shown excellent electrical and optical characteristics, such as large band gap energy of 3.37 eV and large exciton binding energy of 60 meV at room temperature (RT) [9].…”
Section: Introductionmentioning
confidence: 99%
“…When compared to GaN and ZnSe, ZnO films can be deposited at a lower temperature, which is preferable for realizing integration of ZnO based optoelectronic devices using silicon-based microelectronic process. Moreover, it is believed that the Ga, Al and In doped ZnO nanostructures possess more potential for diverse applications [5]. Among these elements, Ga has two major advantages.…”
Section: Introductionmentioning
confidence: 99%